Penile Transplantation in Gender Affirmation Surgery: A Theoretical Feasibility Study - Lopez, Christopher D.; Yusuf, Cynthia T.; Girard, Alisa O.; Lake, Isabel V.; Cooney, Damon S.; Redett, Richard J. (Journal of Reconstructive Microsurgery, 2023)
Background It can be argued that individuals in the transgender and gender nonbinary (TGNB) community suffer from a similar impact on quality of life in the face of gender dysphoria, with psychosocial and physical consequences. Indications for penile allotransplantation for patients wishing to undergo gender affirmation surgery have yet to be elucidated, but technical lessons for feasibility can be gleaned from penis transplants that have already been performed on cisgender males to date.Methods This study investigates the theoretical feasibility for penile-to-clitoral transplantation, prior penile transplants, and current multidisciplinary gender affirmation health care modalities.Results Penile allotransplantation offers a potential solution for individuals in the TGNB community for a more aesthetic penis, improved erectile function without the need of a prosthesis, optimal somatic sensation, and improved urethral outcomes.Conclusion Questions remain about ethics, patient eligibility, and immunosuppressive sequelae. Before these issues are addressed, feasibility of this procedure must be established.
Keywords: penile transplant; microvascular surgery; gender affirmation surgery